Diameter growth of trees in miombo and acacia woodland in an eroded landscape in NE Tanzania - Raw data diameter growth of trees in miombo and acacia woodland, KIH, 1991–2010, Tanzania - Skoglund, Jerry; Backéus, Ingvar; Skarpe, Christina; Hytteborn, Håkan (Swedish University of Agricultural Sciences, 2021)
Diameter growth of 15 tree species in miombo and acacia woodland was monitored. All in all 239 individuals with a diameter >3 cm were measured intermittently from 1991 to 2010, in permanent plots. Growth rate per species was calculated. The study was performed in Kondoa Irangi Hills (KIH), Tanzania, in an area subjected to severe erosion, with the aim to study growth characteristics, and to recommend restoration measures in the absence of fire and grazing.

The dataset displays diameter measurements collected in the field 1991 to 2010. Diameter was measured with a tree caliper in fifteen species, in total 239 inividuals. The datafile has 17 sheets, one per species (one species has two extra sheets). Column 1: species namn in latin, Column 2: individual tree nummer, Column 3: measurement year, Column 4: diameter in cm.

Diametertillväxt hos 15 arter av miombo- och acaciaträd, med en diameter >3 cm, representerade av 239 individer, etablerade i permanenta provytor. Träden mättes med oregelbundna intervall, vid regntidens slut (april), åren 1991 t.o.m. 2010. Tillväxt per art beräknades. Studien genomfördes i Kondoa Irangi Hills (KIH) Tanzania, ett område karakteriserat av svår erosion. Syftet var att studera återväxten, i frånvaro av betesdjur och eld, med syfte att kunna rekommendera restaureringsåtgärder.

Datasetet består av mätvärden insamlade i fält 1991 till 2010. Diametervärden mättes med klave för femton trädarter. Datafilen har 17 blad, ett blad per art (en art återges i två extra blad). Datasetet består av fyra kolumner. Kolumn 1: latinskt artnamn, Kolumn 2: enskilda trädindivids nummer, Kolumn 3: årtal för mätningen, Kolumn, 4: diametervärde i cm.
Diametertillväxt hos träd i miombo och acaciaskog i ett eroderat landskap i nordöstra Tanzania - Grunddata diametertillväxt träd i miombo och acaciaskog, KIH, 1991–2010, Tanzania
Keywords: Habitats and biotopes; Naturtyper och biotoper; Land use; Markanvändning; diameter growth; diametertillväxt; acacia; acacia; Tanzania; Tanzania; miombo; miombo; Natural Sciences; Naturvetenskap; Environmental Sciences; Miljövetenskap; Biological Sciences; Biologi; Botany; Botanik; Ecology; Ekologi; Biota; Biologi och ekologi; Environment; Miljö